Sensitivity and Specificity of the Comfort Scale to Assess Pain in Ventilated Critically Ill Adult Patients in Intensive Care Unit - Wahyuningsih, Indah S; Prasetyo, Awal; Utami, Reni Sulung (Department of Nursing, Faculty of Medicine, Diponegoro University, 2017)
Background: Pain is a common phenomenon experienced by ventilated and critically ill adult patients. It is urgent to measure the pain among these patients since they are unable to report their pain verbally. Comfort Scale is one of the instruments used to measure pain in adult patients. The scale is used to measure pain among children patients with fairly high sensitivity and specificity.Purpose: This study aimed to examine the sensitivity and specificity of the Comfort Scale to measure pain in the ventilated critically ill adult patients in the ICU.Methods: This study employed a cross-sectional design with 66 ventilated adult patients in the ICUs of two hospitals in Semarang. The pain assessment was administered to the patients in 2 duplo periods by two observers comparing with the Comfort Scale and Critical Care Pain Observational Tool (CPOT) as a gold standard instrument during the pre and post positioning procedures. The data were analyzed using the receiver operating curve (ROC).Result: The results showed that in the pre-positioning procedure, the Comfort Scale had the sensitivity value of 69% and the specificity value of 81%. Meanwhile, in the post-positioning procedure, the values were decreasing (the sensitivity of 45%, the specificity of 67%). This indicated that the sensitivity value of the comfort scale decreased and could be interpreted that the ability of the instrument to detect pain remained low. Meanwhile, the decrease of the specificity value of the instrument between the pre and post administration was not far different, so it could be interpreted that the instrument can correctly identify the patient without pain.Conclusion: The Comfort Scale had a lower value of sensitivity and specificity in the post-positioning than that in the pre-positioning procedure. It is recommended that further studies should focus on the relationship between sedation and pain by using instruments of pain studies for adult patients (CPOT). Additionally, the hospital policy makers, that is Pain Task Force is expected to give education and training through workshops and seminars about the nurse skills in pain management on critical areas as part of the multidisciplinary team.